Preparation and study of the luminescent glass-ceramics based on barium iodide activated with Eu2+ - Salamakha, Tatsiana A.; Trusova, Ekaterina E.; Tratsiak, Yauhen U. (Journal of the Belarusian State University. Chemistry, 2019)
In this paper an original method for obtaining glass-ceramics based on barium iodide powder activated with Eu2+ is proposed, their structural and spectral-luminescent properties are investigated. X-ray diffraction analysis has evidenced that glass-ceramics containing BaI2 ∙ 2H2O and BaI2 are formed when 50 mas. % of the starting iodide powder is used in the synthesis process. The possibility of using glass-ceramics for preventing the contact of iodide powder with water vapor has been confirmed.